Benin : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2020)
The Public Investment Management Assessment (PIMA) of Benin has brought to light an institutional framework of high quality but ineffective implementation. In accordance with the PIMA methodology applied in several countries, the mission focused on assessing the institutional strengths for each institution in the analytical framework, as well as its effective implementation. The authorities in 2016 adopted an ambitious investment plan, the government action program (PAG), which is designed to stimulate Benin's economic and social development. Investments in flagship sectors have been identified as means to support this development; the PAG provides recourse primarily to new financing mechanisms, such as public-private partnerships, to ensure the realization of these investments. In connection with the implementation of the PAG, the financial incidences of selected projects should be fully accounted for and reflected in the budget documentation to ensure their sustainability. Enhanced coordination of planning and budget exercises would encourage a better consideration of recurrent expenditure.